KEMAMPUAN APARAT TERHADAP PENGELOLAAN PROGRAM KELUARGA HARAPAN DI KELURAHAN PANRENG KECAMATAN BARANTI - Andi Rismayanti Sappewali; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine the ability of the apparatus to manage the management of the Family Hope Program and to determine the factors that influence the management of the Family Hope Program in Panreng Village, Baranti District. The research population was 3072 people/person and the sample was 97 people/person. The sampling technique used is purposive sampling. This type of research is descriptive quantitative. Data collection techniques used are observation, library research, questionnaires and documentation. Data analysis techniques using statistics, and linear regression. The results showed that the ability of the apparatus was 67% good and the management of the Hope Family Program was 67% good. Based on the results of linear regression analysis, the awareness factor is 9%, the rule factor is 5%, the ability or skill factor is 3% affects the management of the Expected Family Program. Meanwhile, organizational factors do not affect the management of the Family Hope Program in Panreng Village.